Art therapy for maternity and family. One way to support positive parenting - Lucía Hervás Hermida (Arteterapia)
This paper describes the possibilities of art therapy for families as a way of support for positve parenting, fostering the develop of atachmentt, parental competences and resilience. A deep review of the literature is presented, about the model of positive parenting, family art therapy, and specifically art therapy for maternity, from gender perspective. The findings shed light on the potential of art therapy with families and mothers to encourage them to exercise their role as parents satisfactorily, in a process of personal growth.